Employee service performance and collective turnover: Examining the influence of initiating structure leadership, service climate and meaningfulness. (July 2019) - Walumbwa, Fred O; Hsu, I-Chieh; Wu, Cindy; Misati, Everlyne; Christensen-Salem, Amanda
Organizations typically rely on their employees to provide high-quality service as a strategy for sustaining a competitive advantage. However, service-related jobs can have deleterious effects on employees—including negative health and attitudinal outcomes, such as burnout and decreased motivation—which also carry ramifications for organizations, including turnover. How might organizations mitigate these consequences? We posit that organizations can equip managers to create work environments conducive to employee motivation and performance because managers have substantial influence over the context within which service-oriented behaviors occur. Thus, drawing on social information processing theory and theory on work motivation, we build and test a path model that explains how and why an important type of leadership behavior—initiating structure leadership—enhances employees' service performance and reduces collective turnover. Our multilevel analyses using multisource lagged data reveal that initiating structure leader behavior creates a high-quality service climate, which then influences meaningfulness at the individual and work-unit levels. At the individual level, our results show that employee motivation of meaningfulness positively relates to supervisor-rated employee service performance. Finally, results show that collective meaningfulness negatively relates to objective collective turnover as obtained from company archival records. Theoretical and practical implications of our study are discussed.